Pengaruh Strategi Multi Level Marketing, Harga, dan Product Knowledge Terhadap Keputusan Pembelian : Studi Pada Konsumen Produk Herbalife di Bless Fit Club Jombang - Ida Rachmawati; Nurul Hidayatinnisa’ (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of multi-level marketing strategy, prices, and product knowledge on purchasing decisions. This research used causal associative research with a quantitative approach. This study used observation and questionnaires as the data collection techniques. The questionnaires were distributed to 70 respondents, namely all consumers of Herbalife products at Bless Fit Club Jombang. The data analysis used descriptive_analysis, questionnaire test, classical assumption test, multiple regression analysis, analysis of the coefficient of determination and hypothesis testing. The test results show that multi-level marketing strategy and product knowledge have a positive.effect on purchasing decisions, while price does not affect purchasing decisions. The results of this study can be concluded that multi-level marketing strategy, prices, and product knowledge together have a positive effect on purchasing decisions. Herbalife needed to improve communication with consumers. One of them is about the compatibility of price with product quality so that consumers are interested in purchasing Herbalife products. In addition, Herbalife needs to optimize the multi-level marketing and product knowledge strategies that have been implemented so as to influence consumer purchasing decisions.